Cellular Agriculture for Production of Cell-Based Seafood: Part 2— Why should we start with lean fish? - Rose Omidvar; Razieh Farzad (EDIS, 2023)
This EDIS publication is the second in cellular agriculture series in which we provided information on why some fish species are better candidates for cell-based seafood production. In addition, we discussed why zebrafish could be a suitable animal model for the research and development of cell-based seafood.